Pemanfaatan Aplikasi ‘Canva’ Dalam Meningkatkan Hasil Belajar Menulis Teks Tanggapan Peserta Didik Kelas VII C SMPN 4 Madiun - Ella Wahyu Novitasari; Eni Winarsih; Sri Andayani (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This research aims to utilize Canva learning media to improve learning outcomes for class VII C SMPN 4 Madiun on response text material. This research is a Class Action research (PTK) showing the effectiveness of the Canva media in improving students' learning completion results in the Pre-Cycle, Cycle I and Cycle II phases. It was found that student learning outcomes in diagnostic assessments only reached 3% and 9% increased to 90% when the application of Canva media was combined with a content differentiation and product differentiation approach. The data collection technique uses document analysis in the form of learning results of class VII C students at SMPN 4 Madiun which went through a validity test by the Indonesian language subject teacher. So the use of Canva learning media in response text material has been proven to improve student learning outcomes.